(3GdNOeGJ GdHfcjI GdEdcJQhfjI YHQ GdEfJQfJ (B=s Electronic banking services via internet - (3CHh aQhI, eMehO eMeOs ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2012)
(3JYJHQ GdHfhc EMOi Cge GdQcGFR GdJj jbhe YdjgG GdGbJUGO GdhWfj aj eNJda GdOhd, fJjLI ddOhQ GdcHjQ GdPj Jbhe Hg aj JYHFI GdeONQGJ ef GdLeghQ hhVYgG Qgf ETGQI GdeTQhYGJ hGdGSJKeGQGJ GdOGNdjI hGdNGQLjI ddOhdI, hHGdJGdj aEf Jdbj GdhOGFY hefM GdGFJeGf jTcd GdfTGW GdQFjSj ddHfhc, EdG Cfg dG jTcd GdfTGW GdhMjO dgG, aHGdehGRGI eY Pdc Jbhe GdHfhc HeLehYI CNQi ef GdhXGFa GdgOa efgG JhajQ GdhSGFd GdedGFeI ddJYGed aj GdMSGHGJ MSH eJWdHGJ cd aFI ef aFGJ YedGFgG, aGdJGLQ jJhbY ef Hfcg JbOje NOeGJ JSgd dg CYeGdg GdJLGQjI, HjfeG jHMK ZjQ GdJGLQ Yf GdHfc GdPj jhaQ dg eeGQSI CYeGdg GdHfcjI HCbd JcdaI hOhf JYbjO Ch JCNjQ(B. (3hbO TgOJ GdYbhO GdCNjQI JWhQGJ JcfhdhLjI CMOKJ JCKjQG cHjQG HWQjbI Ch HCNQi aj LejY fhGMj GdMjGI, hHGdNUhU aj bWGYGJ GdfTGW GdGbJUGOj GdeNJdaI hef HjfgG GdbWGY GdHfcj, MjK TQYJ GdHfhc aj GdGSJaGOI ef Jdc GdJWhQGJ dGSJNOGegG aj JbOje GdNOeGJ fXQG ddahGFO GdeJQJHI YfgG, hbO COi GdGfJTGQ GdhGSY GdPj YQaJg HYV GdNOeGJ GdHfcjI GdfGJLI Yf GdJWhQ GdJcfhdhLj ceG gh TCf GdHWGbGJ GdHfcjI, Edi Jchjf bfGYI dOi GdHfhc eaGOgG Cf GdGSJaGOI ef GdJcfhdhLjG GdMOjKI dJbOje GdNOeI GdHfcjI CeQ dG Zfi Yfg aj Xd GdefGaSI GdTOjOI GdJj jTgOgG GdbWGY GdHfcj(B.s
(3GdCUd CWQhMI eGLSJjQ HETQGa GdOcJhQ YHO GdYRjR MVQj(B.s
(3HHdjhLQGajI (B: (3UaMI (B217-240.s
Keywords: (3GdNOeGJ GdeUQajI YHQ GdEfJQfJs; (3GdHfhcs -- (3eYGdLI HjGfGJs